The Price is Not Always Right : On the Impacts of (Commodity) Prices on Households (and Countries) - Lederman, Daniel (World Bank, Washington, DC, 2014)
This paper provides an overview of the impact of once-and-for-all changes in commodity prices and other prices on household welfare. It begins with a collection of stylized facts related to commodities based on household survey data from Latin America and Africa. The data uncover strong commodity dependence in both continents: households typically allocate a large fraction of their budget to commodities and they often depend on commodities to earn their income. This income and expenditure dependency suggests sizable impacts and adjustments following commodity-price shocks. The paper explores these effects with a review of the literature. It studies consumption and income responses, labor-market responses, and spillovers across sectors. It ends up providing evidence on the relative magnitudes of various mechanisms through which commodity prices affect household (and national) welfare in developing economies.